Software for Creating Tutorials and Examinations on Natural Languages - Dolmatova, Polina; ., . (International Journal of Engineering and Technology, 2018)
Currently, philologists often use various software in studying and testing foreign languages. This work presents the software for creating tutorials and exams by philologists independently from software developers. To cover various features of natural languages and involve more abilities of users, such tutorials and exams contain randomly generated tasks of different types. Both questions and answers of the tasks can be text, graphic, sound, or combined. This software implements the algorithmic programming language for creating randomly generated (parameterized) tasks. The paper describes the objects, the syntax, and the procedure for generating random tasks in this programming language. The developed software is tested and used in secondary and higher educational institutions.Â Â